2018
DOI: 10.1182/bloodadvances.2017013979
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase 2 trial of monthly vitamin D to prevent respiratory complications in children with sickle cell disease

Abstract: In sickle cell disease, respiratory infection and asthma may lead to respiratory complications that are a leading cause of morbidity and mortality. Vitamin D has anti-infective and immunomodulatory effects that may decrease the risk for respiratory infections, asthma, and acute chest syndrome. We conducted a randomized double-blind active-controlled clinical trial to determine whether monthly oral vitamin D can reduce the rate of respiratory events in children with sickle cell disease. Seventy sickle cell subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 60 publications
0
29
1
2
Order By: Relevance
“…For children with HbSS, vitamin supplementation improved their clinical status with increased fetal hemoglobin, decreased inflammatory status, and reduced platelet counts (Dougherty et al, 2015). A 2-year supplementation (monthly oral 100,000 or 12,000 IU) study improved annual rates of respiratory illness in children aged 3−20 years with SCD (reduction of > 50%; Lee et al, 2018). Although other vitamin D supplementation trials in SCD have been conducted, many have not been of sufficient size or quality to inform clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For children with HbSS, vitamin supplementation improved their clinical status with increased fetal hemoglobin, decreased inflammatory status, and reduced platelet counts (Dougherty et al, 2015). A 2-year supplementation (monthly oral 100,000 or 12,000 IU) study improved annual rates of respiratory illness in children aged 3−20 years with SCD (reduction of > 50%; Lee et al, 2018). Although other vitamin D supplementation trials in SCD have been conducted, many have not been of sufficient size or quality to inform clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…30 Since the date of the final literature search performed for that study (December 2015), fifteen RCTs with 19,569 participants fulfilling the same eligibility criteria have been completed and analysed. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] We therefore sought data from these more recent studies for inclusion in an updated metaanalysis of aggregate (trial-level) data to determine whether vitamin D reduced ARI risk overall, and to evaluate whether effects of vitamin D on ARI risk varied according to baseline 25(OH)D concentration and/or dosing regimen (frequency, dose size, and trial duration).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted in children confirmed our findings of significant association between VDD and increased risk of viral and bacterial respiratory tract infections [ 37 39 ]; Urashima and colleagues even suggest that vitamin D supplementation plays a role in prevention of seasonal influenza [ 40 ]. Other authors encounter more than 50% reduction of the respiratory illness rate on the second year of monthly vitamin D supplementation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%